Cybergogy Theory Approach in the Implementation of Inclusive Education in Higher Education: A Literature Study - Jatiningsiwi, Tata Gading; Ediyanto, Ediyanto; Ummah, Umi Safiul (Angstrom Centre of Education, 2024)
The implementation of inclusive education cannot be separated from the times. Currently, the era of massive use of technology, including in the scope of education. The purpose of this study is to examine the theory of cybergogy about inclusive education in higher education. The method used is a systematic review of the literature. The literature review was conducted by selecting articles from journals published within 5 years (2020-2024). The steps taken in this research are plan review, conduct review, and document review. The results of the literature study revealed that the cybergogy learning strategy significantly impacts students' learning experience. The cybergogy model activates cognitive, emotional, and social factors, and influences participation in online learning. However, there is still little literature that discusses the implementation of inclusive education using the cybergogy approach. Even though there are many studies on the use of technology in education, it seems that the application of cybergogy theory to inclusive education in higher education has not received much attention. Based on the analysis of the basic principles of cybergogy, there is an opportunity to combine the cybergogy approach with its implementation in inclusive education in higher education.